Harmonisasi Dimensi Tasawuf dan Rasionalitas Kontemporer dalam Pembelajaran Pendidikan Agama Islam Holistik: sintesis antara logika kontemporer dan spiritualitas dalam pembelajaran PAI - Divan Haizul Ulum; Nur Jannah (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
Islamic Religious Education (IRE) in the contemporary era faces significant challenges due to the dominance of instrumental rationality, rapid technological advancement, and moral-spiritual crises, which have shifted educational practices toward cognitive achievement while neglecting character formation and spiritual development. These conditions require an educational paradigm capable of integrating intellectual, spiritual, moral, and social dimensions in a balanced manner. This study aims to examine the concept of holistic Islamic Religious Education through the synthesis of Sufism and contemporary rationality as an educational paradigm relevant to modern challenges. The research employed a qualitative approach using a library research method. Data were collected from classical and contemporary literature on Islamic educational philosophy, Sufism, holistic education, and the thoughts of scholars such as Al-Ghazali, Syed Muhammad Naquib Al-Attas, and contemporary educational thinkers. The findings indicate that integrating Sufistic values with contemporary rationality produces a holistic Islamic educational paradigm that harmonizes intellectual, spiritual, emotional, and social competencies. This paradigm contributes to developing learners who are knowledgeable, morally grounded, critically minded, adaptable to contemporary developments, and spiritually conscious in responding to the complexities of modern life.